2017
DOI: 10.1093/sleep/zsx163
|View full text |Cite
|
Sign up to set email alerts
|

Circadian Phase and Phase Angle Disorders in Primary Insomnia

Abstract: Objectives:We aimed to identify the prevalence of circadian phase and phase angle abnormalities in patients with insomnia. Methods: We conducted a cross-sectional, multicenter study at three sleep laboratories in the United States and Australia. Patients with insomnia and healthy control participants completed a sleep log for 7 days. Circadian phase was assessed from salivary dim light melatonin onset (DLMO) time during a 12-hour laboratory visit. Results: Seventy-nine patients meeting the Research Diagnostic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
51
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(55 citation statements)
references
References 43 publications
3
51
0
1
Order By: Relevance
“…DSPD patients are often miscategorised as insomnia patients, due to seemingly similar presentations when adequate sleep opportunity at the desired sleep time is not present [ 1 , 3 ]. A recent study reported that up to 22% of insomnia patients have abnormal circadian timing relative to the sleep-wake cycle, suggesting a circadian mechanism for their sleep disturbances [ 25 ]. Further, the two phenotypes of DSPD receive the same clinical diagnosis based on behavioural symptomology, despite exhibiting distinct physiology (i.e., differences in circadian timing).…”
Section: Discussionmentioning
confidence: 99%
“…DSPD patients are often miscategorised as insomnia patients, due to seemingly similar presentations when adequate sleep opportunity at the desired sleep time is not present [ 1 , 3 ]. A recent study reported that up to 22% of insomnia patients have abnormal circadian timing relative to the sleep-wake cycle, suggesting a circadian mechanism for their sleep disturbances [ 25 ]. Further, the two phenotypes of DSPD receive the same clinical diagnosis based on behavioural symptomology, despite exhibiting distinct physiology (i.e., differences in circadian timing).…”
Section: Discussionmentioning
confidence: 99%
“…Circadian dysfunction has been associated with several chronic disease states, including mood disorders ( 10 , 28 ), metabolic and cardiovascular disease ( 29 ) and sleep disorders ( 11 , 14 , 30 ). Abnormalities in circadian light sensitivity may be a trait vulnerability for mood disorders with variable or decreased sensitivity being observed in seasonal affective disorder ( 12 ), while hypersensitivity to light has been observed in bipolar disorder ( 10 , 28 ), and in some sleep disorders or disturbances ( 11 , 31 ).…”
Section: Discussionmentioning
confidence: 99%
“…Even among individuals living in the same social time zone and maintaining the same sleep‐wake rest‐activity schedules, there are wide ranges in circadian time (~5 hours in healthy young individuals, 2 ~8 hours in people with insomnia, 3 and even more dramatic differences in patient populations, including patients with circadian rhythm sleep disorders (eg, some individuals with delayed sleep phase syndrome 4 and free‐running or abnormally entrained blind individuals 5 ). There may be several reasons for this wide range in circadian time relative to social time, including individual differences in behavior (eg, self‐selected light exposure patterns from both natural [including different seasons] and artificial sources 6,7 ) and genetic factors 8 related to sleep and circadian regulation.…”
Section: Social Time Does Not Equal Circadian Timementioning
confidence: 99%